A handwriting document encryption scheme based on segmentation and chaotic logarithmic map. (21st April 2021) - Abu-Amara, Fadi; Bensefia, Ameur
A one-dimensional chaotic logarithmic map (CLM) is proposed. Characteristics of the CLM are investigated and used to develop a symmetric handwriting document encryption scheme that consists of three phases. The segmentation phase divides a handwriting image into graphemes. The permutation phase shuffles pixel locations of each grapheme. Finally, the substitution phase modifies pixel intensity values of the corresponding permutated grapheme utilising the chaotic logarithmic map. Experimental results indicate that the proposed CLM poses interesting characteristics such as wide range chaotic behaviour, robust chaos, s-unimodality, and high sensitivity to a small change in initial condition. The results also indicate that the randomly generated keystreams by the CLM pass the NIST statistical tests. Furthermore, the proposed segmentation and encryption scheme achieves a key space of 2 180 and provides a high encryption performance for handwriting documents. In addition, statistical results indicate the superior permutation and substitution properties of the proposed encryption scheme over other image encryption schemes of the same structure.